Truth and fiction in The Da Vinci code : a historian reveals what we really know about Jesus, Mary Magdalene, and Constantine - Ehrman, Bart D. (OUP E-Books., 2004)
A biblical historian examines the history of the early Christian church that forms the background for "The Da Vinci Code," pointing out inaccuracies in the novel and providing an introduction to biblical scholarship.